Peran Guru Bimbingan Konseling Dalam Pembentukan Karakter Disiplin Siswa SMK Ma’arif Nu 1 Purbolinggo - Della Rosita; Anita Oktaviana; Diah Ayu Setianingsih (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This research aims to determine the role of guidance and counseling teachers in forming the disciplined character of students at SMK Ma'arif Nu 1 Purbolinggo. This research uses a descriptive qualitative approach. Researchers used data collection methods in the form of interviews and documentation of determining informants in this study using purposive sampling techniques. The informants in this research were student representatives, homeroom teachers, guidance and counseling teachers and one student in class Guidance and counseling teachers collaborate with student representatives, homeroom teachers, and parents to solve problems of students who lack discipline. Students who lack discipline are given individual counseling services and guidance and counseling teachers also make visits to students' homes to find out the factors causing the students' lack of discipline and discuss student problems at school with the students' parents.